Aktivitas Mikroorganisme Pada Tanah Bekas Erupsi Gunung Sinabung Di Kabupaten Karo - Puput Sarah; Deni Elfiati; Delvian Delvian (Program studi Kehutanan USU, 2015)
Volcanic ash released when the eruption has an acidic pH, thus affecting the amount and activity of microorganisms in the soil. Therefore conducted this study to determine the activity of soil microorganisms in the former eruption of Mount Sinabung in Karo. Measurement of total soil microorganisms was done by Agar Cawan method, while the measurement of the activity of soil microorganisms was conducted jar and titrimetic method. The result of the research showed that the higher of the pH, the colony of microorganism will be much and the reverse. The higher of C- organic, the activity of micoorganism will be high within the soil, and the reverse. Respiration value on land affected by volcanic ash at a depth of 0-5 cm was 0,96. Respiration value on land affected by volcanic ash at a depth of 5-20 cm was 1,16. Respiration value on land that was not affected by volcanic ash was 1,52.Keywords: Volcanic ash, soil microorganisms, microorganism activity, soil depth.